Evolving Impacts of Life Skills training on Adolescent Aggression: A comparative Review across Decades (ShodhVarta, 2024)
This paper provides a comprehensive review of life skills training (LST) programs and their impact on adolescent aggression across four decades, from 1980 to 2020. By systematically analyzing a wide range of studies, the paper traces the evolution of LST interventions, examining their effectiveness, challenges, and areas needing improvement. The methodology involved a rigorous literature review using extensive searches in reputable academic databases such as PubMed, PsycINFO, and ERIC. Studies were carefully selected based on their relevance to the topic, publication date, and methodological soundness. The inclusion criteria required that all studies be peer-reviewed, published between 1980 and 2023, and directly address the relationship between life skills training and adolescent aggression. The data synthesis employed a thematic analysis approach, organizing the findings by decade to uncover trends, shifts, and persistent gaps in the literature. This review not only identifies critical gaps in current research but also offers recommendations for future studies. It underscores the importance of developing more culturally sensitive interventions, incorporating technological advancements, and considering contextual factors such as culture and socioeconomic status in the design of LST programs. These insights aim to guide future research and enhance the effectiveness of interventions targeting adolescent aggression.